Nutritional quality of food consumed (graded by the FSAm-NPS / Nutri-Score) and mortality in Europe. (13th November 2019) - Deschasaux, M; Huybrechts, I; Murphy, N; Julia, C; Hercberg, S; Srour, B; Ferrari, P; Riboli, E; Gunter, M; Touvier, M
Abstract: Background: Unhealthy diets are major contributors for non-communicable diseases (NCDs) and related deaths. To help consumers make healthier food choices, political authorities are considering implementing a simple label to reflect the nutritional quality of food products. The Nutri-Score, based on the nutrient profiling system of the Food Standards Agency (FSAm-NPS), was chosen by several countries in Europe (France, Belgium, Spain). Yet, its implementation is only voluntary per EU regulation. Scientific evidence is therefore needed regarding the relevance of the FSAm-NPS at the European level. Hence, our objective is to study how the nutritional quality of foods consumed graded by the FSAm-NPS relates to NCDs-related mortality in European populations. Methods: Our prospective analyses included 501, 594 adults from the EPIC cohort (1992-2015, median follow-up: 17.2y). Usual food intakes were assessed with standardized country-specific methods. The FSAm-NPS was calculated using the 100g content of each food in energy, sugar, saturated fatty acid, sodium, fibres, proteins, and fruits/vegetables/legumes/nuts. Multi-adjusted Cox proportional hazards models were computed. Results: The consumption of foods with a higher FSAm-NPS score (lower nutritional quality) was associated with a higher risk of mortality overall (n = 50, 743 events: HRQ5vs.Q1=1.06 [95%CI: 1.02-1.09], P-trend<0.001) and by cancer (n = 21, 971 events: HRQ5vs.Q1=1.06 [1.01-1.11], P-trend=0.003), respiratory diseases (n = 2, 796 events: HRQ5vs.Q1=1.33 [1.16-1.52], P-trend<0.001) and cardiovascular diseases, although more weakly (n = 12, 407 events: HRQ5vs.Q1=1.05 [0.98, 1.11], P-trend=0.04). Conclusions: In this large multinational European cohort, consuming foods with a higher FSAm-NPS score was associated with higher mortality, supporting the relevance of the FSAm-NPS to grade the nutritional quality of food products for public health applications (e.g, Nutri-Score) to guide the consumers towards healthier food choices. Key messages: The consumption of food products with a lower nutritional quality as graded by the FSAm-NPS score was associated with higher mortality in the large multinational European EPIC cohort. This adds support to the relevance of the FSAm-NPS to grade the nutritional quality of foodstuffs for public health applications (e.g. Nutri-Score label) to help consumers make healthier food choices.